User Interface Design And User Experience Kuysedekah.Id Mobile Applications - Moh Ahsan; Wahyudi Arianto; Robbi Tri Murdani (LPPM UBHINUS MALANG, 2020)
The population of Indonesia is very Muslim, so there are many mosques in Indonesia. Many people raise funds directly on the road, but not infrequently this activity actually hinders the mobility of road users such as congestion and lack of light on funds. An innovative application prototype for alms that is easy and based on user desires. The Kuysedekah.id application design development model based on Mobile App. The UI (User Interface) and UX (User Experience) design prototypes aim to produce good results, and can meet the needs of smartphone users (user friendly), design thinking, and test prototypes. UX assessment uses a design review with a